Identification of nitric oxide in mitochondria of myometrium cell - Danylovych, Yu.V.; Karakhim, S.A.; Kolomiets, O.V.; Danylovych, G.V.; Kosterin, S.O. (Вiopolymers and Cell, 2015)
Aim. To demonstrate the possibility of NO synthesis in intact myocytes of uterus. Methods. Confocal scanning microscopy method, NO-sensitive fluorescent probe DAF-FM, MitoTracker Orange CM-H2TMRos. Results. The basal production of NO in intact myocytes was shown using DAF-FM. Incubation of myocytes with NO donor – sodium nitroprusside (SNP) – led to an increase of the DAF-FM-T fluorescent signal. On the contrary, the addition of NO-synthase inhibitor – N-nitro-L-arginine (NA) – results in the reduction of fluorescent intensity. It was demonstrated colocalizition of specific probe for mitochondria MitoTracker Orange CM-H2TMRos and NO-sensitive dye DAF-FM. Conclusions. For the first time it has been demonstrated the presence of NO in smooth muscle cell mitochondria using laser confocal microscopy, NO-sensitive probe DAF-FM and specific marker of the functionally active mitochondria MitoTracker Orange CM-H2TMRos. Мета. Продемонструвати можливість синтезу NO в інтактних міоцитах матки щурів. Методи. Конфокальна скануюча мікроскопії, NO-чутливий флуоресцентний зонд DAF-FM, MitoTracker Orange CM-H2TMRos. Результати. Показано базальну продукцію NO в інтактних міоцитах за допомогою флуоресцентного зонду DAF-FM. Внаслідок інкубації клітин з донором NO нітропрусидом натрію (SNP) спостерігалось зростання флуоресцентного сигналу DAF-FM-T. І навпаки, внесення інгібітора NO-синтази – N-нітро-L-аргініну (NA) – призводило до гасіння флуоресценції. Доведено колокалізацію флуоресцентного мітохондріального маркеру MitoTracker Orange CM-H2TMRos та NO-чутливого зонду DAF-FM. Висновки. Вперше показано наявність NO в гладеньком’язових клітинах матки, і зокрема в мітохондріях, із залученням методу лазерної конфокальної мікроскопії, NO-чутливого зонду DAF-FM та специфічного маркеру функціонально активних мітохондрій MitoTracker Orange CM-H2TMRos. Цель. Продемонстрировать возможность синтеза NO в интактных миоцитах матки крыс. Методы. Конфокальная сканирующая микроскопии, NO-чувствительный флуоресцентный зонд DAF-FM, MitoTracker Orange CM-H2TMRos. Результаты. Показана базальная продукция NO в интактных миоцитах с использованием флуоресцентного зонда DAF-FM. Инкубация миоцитов с донором NO – нитропруссидом натрия (SNP) – приводила к повышению флуоресцентного сигнала DAF-FM-T. И наоборот, внесение ингибитора NO-синтазы – N-нитро-L-аргинина (NA) – снижало интенсивность флуоресценции. Показана колокализация флуоресцентного митохондриального маркера MitoTracker Orange CM-H2TMRos и NO-чувствительного зонда DAF-FM. Выводы. Впервые показано присутствие NO в гладкомышечных клетках матки, в частности митохондриях, с использованием метода лазерной конфокальной микроскопии, NO-чувствительного зонда DAF-FM и специфического маркера функционально активных митохондрий MitoTracker Orange CM-H2TMRos.